If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -5) + (8x + -13) = 180 Reorder the terms: (-5 + 3x) + (8x + -13) = 180 Remove parenthesis around (-5 + 3x) -5 + 3x + (8x + -13) = 180 Reorder the terms: -5 + 3x + (-13 + 8x) = 180 Remove parenthesis around (-13 + 8x) -5 + 3x + -13 + 8x = 180 Reorder the terms: -5 + -13 + 3x + 8x = 180 Combine like terms: -5 + -13 = -18 -18 + 3x + 8x = 180 Combine like terms: 3x + 8x = 11x -18 + 11x = 180 Solving -18 + 11x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 18 + 11x = 180 + 18 Combine like terms: -18 + 18 = 0 0 + 11x = 180 + 18 11x = 180 + 18 Combine like terms: 180 + 18 = 198 11x = 198 Divide each side by '11'. x = 18 Simplifying x = 18
| 5u+18=58 | | (3d+4)+(2d-9)=180 | | 4b-6+2r=-48 | | 3x+12=5x+42 | | a+2s=3(s-2)+1 | | x^2+17x-193=0 | | t=x^2+3x | | 2a^2+23a+45=0 | | 8(-38x+32)=-43(-21+8x) | | 10(x+1)-4v=3(2v+3)-11 | | 3n-4=2n | | 1.1x-1.62=-1.4 | | 3x+7=7-(4x-9) | | 5.75+5-k= | | x=t^2+3t | | 800x=100x^2 | | 2(5x+3)=98+3x | | 9(8z+9)+6=-273 | | -6(x-7)-7=-7x+2 | | -2.5--0.7=x | | 1.1x=3y-0.4 | | 3p+3.7=9.1 | | -13=x+72 | | n-5=-13 | | .2(x+3)-.5(x+3)=-0.3-0.9 | | 496=62x | | 3/8c=6 | | (n-7)-2n=12 | | 10-2(x+10)=60 | | 7x-1=23+7x | | x+4.07=6.46 | | 6x+6=11-2x |